Staff Guidance Note on the Application of the Joint Fund-Bank Debt Sustainability Framework for Low-Income Countries (LICs). (Policy Papers; Policy Paper ;, 2007)
The guidance note covers analytical aspects of the DSA framework, including the main changes introduced in this note. It also discusses DSA design and operational implications and technical modalities for preparing DSAs including timing, information sharing, review, and clearance. It outlines arrangements for HIPCs and discusses a communications strategy. An annex provides a user's guide to the templates.